Effective pulmonary delivery of an aerosolized plasmid DNA vaccine via surface acoustic wave nebulization - Rajapaksa, Anushi E (BioMed Central, 2014)
BACKGROUND: Pulmonary-delivered gene therapy promises to mitigate vaccine safety issues and reduce the need for needles and skilled personnel to use them. While plasmid DNA (pDNA) offers a rapid route to vaccine production without side effects or reliance on cold chain storage, its delivery to the lung has proved challenging. Conventional methods, including jet and ultrasonic nebulizers, fail to deliver large biomolecules like pDNA intact due to the shear and cavitational stresses present during nebulization. METHODS: In vitro structural analysis followed by in vivo protein expression studies served in assessing the integrity of the pDNA subjected to surface acoustic wave (SAW) nebulisation. In vivo immunization trials were then carried out in rats using SAW nebulized pDNA (influenza A, human hemagglutinin H1N1) condensate delivered via intratracheal instillation. Finally, in vivo pulmonary vaccinations using pDNA for influenza was nebulized and delivered via a respirator to sheep. RESULTS: The SAW nebulizer was effective at generating pDNA aerosols with sizes optimal for deep lung delivery. Successful gene expression was observed in mouse lung epithelial cells, when SAW-nebulized pDNA was delivered to male Swiss mice via intratracheal instillation. Effective systemic and mucosal antibody responses were found in rats via post-nebulized, condensed fluid instillation. Significantly, we demonstrated the suitability of the SAW nebulizer to administer unprotected pDNA encoding an influenza A virus surface glycoprotein to respirated sheep via aerosolized inhalation. CONCLUSION: Given the difficulty of inducing functional antibody responses for DNA vaccination in large animals, we report here the first instance of successful aerosolized inhalation delivery of a pDNA vaccine in a large animal model relevant to human lung development, structure, physiology, and disease, using a novel, low-power (<1 W) surface acoustic wave (SAW) hand-held nebulizer to produce droplets of pDNA with a size range suitable for delivery to the lower respiratory airways.